Dietary supplementation with Mexican foods, Opuntia ficus indica, Theobroma cacao, and Acheta domesticus: Improving obesogenic and microbiota features in obese mice - Rosas-Campos, Rebeca; Meza-Rios, Alejandra; Rodriguez-Sanabria, J. Samael; Rosa-Bibiano, Ricardo De la; Corona-Cervantes, Karina; García-Mena, Jaime; Santos, Arturo; Sandoval-Rodriguez, Ana; Armendariz-Borunda, Juan (Frontiers in Nutrition, 2022)
An obesogenic diet high in saturated-fats and sugars, is a risk factor for the development of multiple obesity-related diseases. Our aim was to evaluate the effect of supplementation with a mixture of Mexican functional foods (MexMix): Optuna ficus indica (nopal), Theobroma cacao and Acheta domesticus (edible crickets) over a high fat and fructose/sucrose diet inducing an obesogenic mice model. Eighteen male C57BL/6J mice were divided into three groups. 1) control group: Normal diet (ND). 2) HF/FS Group: High-fat diet plus 4.2% fructose/sucrose and ad libitum water and 3) therapeutic group (MexMix): HF/FS-diet up to week eight and switched for 8 additional weeks to HF/FS-diet supplemented with 10% nopal, 10% cocoa and 10% cricket. MexMix mice showed significant reduced body weight, liver weight, visceral fat, and epididymal fat compared to HF/FS. Levels of triglycerides, cholesterol, LDL, insulin, glucose, GIP, leptin, PAI-1 and resistin were also clearly reduced. Regarding the gut microbiota in the model, 16S rRNA gene sequencing analysis was used, and it was found that MexMix consumption increased the abundance of Lachnospira, Eubacterium coprostanoligenes group and Blautia which are bacteria involved in multiple metabolic beneficial effects. Noteworthy, mice supplemented with MexMix improved cognitive parameters evaluated by Novel Object Recognition test. Therefore, MexMix food supplementation might represent a potential strategy for the treatment of obesity and other diseases associated with excessive consumption of fat and sugars.